Investigasi Perilaku Spontan Individu Saat Bencana Alam: Dalam dan Luar Bangunan - Ulfa Mazaya; Rahmi, Marlisa; Kusuma , Hanson Endra (EMARA: Indonesian Journal of Architecture, 2020)
Indonesia is prone to natural disasters that can occur unexpectedly and gradually. Natural disasters implement surprising impacts due to a lack of awareness and preparedness in facing the threats. One of the reasons caused by such a disaster that can be seen is through human behaviour. Human behaviour is challenging to predict in an emergency, stressful and chaotic. Spontaneous behaviour is distinguished by location factors, indoor or outdoor, with indoor, divided by Home and Public Building. This research aims to reveal spontaneous human behaviour during natural disasters while inside and outside the building. This research was conducted with a qualitative exploratory method. Data were collected using an online questionnaire with open-ended questions and distributed freely. The findings show tendencies to withstand when in the public building while going to distance themselves from building while at home, as for those outdoor opt to surrender as not to do anything